Leverage, corporate governance and real earnings management: Evidence from Korean market - Ana Tulcanaza-Prieto; Young Hwan Lee; Jeong-Ho Koo (Global Business & Finance Review (GBFR), 2020)
Purpose: This study examines how corporate governance (CG) and leverage simultaneously influence real earnings management (REM). Methodology: We employed CG score (CGS), total, short-term, and long-term debt ratios as independent variables, and REM metrics as dependent variables. We include ordinary least-squares (OLS) panel data regressions, residual test, and interaction analysis in our study. Findings: While a significant positive relationship existed between leverage and REM, CG had a negative effect on real manipulations. Our results from the interaction analysis and residual test show that CG is a key player in explaining the relationship between leverage and REM. We also find that firms with a low-level of CG were more likely to conduct REM activities than those with a high-level CG. Research limitations/implications: These results imply that the reduction in opportunistic behavior of managers in the presence of strong CG could decrease the leverage of firms and REM activities and improve the quality of their earnings. Moreover, shareholder rights and audit organizations were the prominent CG characteristics influencing REM activities, as they enforce additional monitoring of financial reporting quality and increase audit standards. CG strategies mitigate the corporate corruption scandals through the adoption of high-quality accounting and financial norms in reporting and management. Thus, executives decrease their incentives to conduct REM activities and leverage cannot be used freely as a mechanism to manipulate earnings, given firms' leverage position is audited and reviewed by the financial committee in firms with strong CG. For future research, the authors suggest including the degree of leverage as a disaggregation sample and adding the degree of cost stickiness. Originality/value: Several s tudies have investigated e ither the relationship between ( 1) REM and leverage, or ( 2) REM and CG, including leverage as a control variable. Our study, extends this bilateral relationship to simultaneous relationship between leverage, CG, and REM. Moreover, we investigate the predominant CG characteristics that influence the association among leverage and REM. We conduct interaction analysis and residual effect to investigate if CG should be considered as a determinant variable in the recurrence of REM activities of managers. We include firms with high- and low- levels of CG to show which firms are leveraged.
Keywords: 650; Real earnings management; Corporate governance; Leverage